(untitled) (Journal of Laboratory Animal Science, 2024)
Successful breeding programme of laboratory animals is one of a key factor in any facility operations. In-house breeding of laboratory animal species depends on using correct breeding method, number of animals requested by the researchers, litter size, birth weight, perinatal mortality, weaning percentage, female:male ratio, parity interval, fostering, postpartum heat, non-productive breeders, enrichment programme etc. To fulfil the animal demands for in vivo research, these points play significant role, especially perinatal mortality. Perinatal mortality is strain dependent and therefore facility must be aware about the percentage of pups mortality to avoid further miscalculation while setting up the breeding program. In order to get the first hand information about strain wise perinatal mortality, historical control data or baseline data should be generated which play an important role in successful breeding programme and timely meeting the target of providing experimental animals. Aim of the present study was to generate baseline control values of reproductive efficiency parameters of commonly used mice strains at ACTREC Animal Facility. The existing in-house data was compiled for the period of July to December 2019. Perinatal mortality varied between the primiparous and multiparous females. In total, data of 4247 pups obtained from 39 inbred primiparous, 93 outbred primiparous, 159 inbred multiparous and 466 outbred multiparous females. The average number of pups delivered by inbred primiparous and multiparous females was recorded as 5.13 and 5.85, respectively. There was no significant difference between the female:male ratio between primiparous and multiparous females of C57BL/6 inbred strain. Weaning of pups was done on day 21. Percentages of weaning of pups from primiparous and multiparous inbred strain were recorded as 87 and 92.37%, respectively. Perinatal mortality in inbred primiparous female was 13% while in inbred multiparous was 7.63%. It is observed that perinatal mortality in inbred primiparous pups is higher than inbred multiparous females. In case of outbred stock of C57BL/6 mice, we observed average litter born of 4.96 and 5.70 for primiparous and multiparous mothers, respectively. Weaning percentage of 83.73% and 93.56% was recorded in outbred primiparous and multiparous mothers, respectively. Perinatal mortality in pups obtained from outbred primiparous and multiparous mothers was 15.84% and 6.44% respectively. The data indicated that perinatal mortality is significantly high in the pups obtained from primiparous females than multiparous females of both the breeding methods. We compared the data of C57BL/6 mice with robust strain, B6D2F1. The overall results can be used as baseline data for our C57BL/6 and B6D2F1 strains by the ACTREC scientists as well as colony managers from other facilities.